2018
DOI: 10.3390/s18020393
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Operational Amplifier with Load-Insensitive Stability Compensation for High-Precision Transducer Interface

Abstract: High-resolution electronic interface circuits for transducers with nonlinear capacitive impedance need an operational amplifier, which is stable for a wide range of load capacitance. Such operational amplifier in a conventional design requires a large area for compensation capacitors, increasing costs and limiting applications. In order to address this problem, we present a gain-boosted two-stage operational amplifier, whose frequency response compensation capacitor size is insensitive to the load capacitance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The amplifiers in [51,52] achieve pseudo single-stage behavior by reducing the impedance of inner amplifier nodes to push the non-dominant poles to high frequencies. The required DC gain is restored by using shunt gain booster circuits, as shown in Figure 9.…”
Section: Other Compensation Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplifiers in [51,52] achieve pseudo single-stage behavior by reducing the impedance of inner amplifier nodes to push the non-dominant poles to high frequencies. The required DC gain is restored by using shunt gain booster circuits, as shown in Figure 9.…”
Section: Other Compensation Architecturesmentioning
confidence: 99%
“…Architectures that rely on reverse nested Miller provide an improved power efficiency [3,13,[29][30][31][32][33] but it has been recognized that nesting Miller capacitors leads to bulky and slow implementations and many architectures were devised to use a single Miller capacitor along with some ancillary compensation structures [4,11,14,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Some authors have also demonstrated compensation techniques that do not rely on a Miller capacitor at all [8,[49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Typical requirements for the sensors are a simple structure, wide bandwidth, reliability, low-Temperature Coefficient of Resistance (TCR), low self-heating, and robustness in sensing environment. In the case of transducers, is required a high precision interface insensitive to load and excellent stability from DC to kHz range [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%